Mechanism of Legal Protection Against the Eradication of The Crime of Human Trafficking - Hendriyanto Butota (Universitas Negeri Gorontalo, 2022)
This study aims to analyze how the protection of human trafficking is in the Law on the Eradication of the Crime of Human Trafficking, and to examine the ideal protection mechanism for human trafficking. This type of research in writing this proposal is a normative juridical research method. The approach used in this study is statutory. The results show that legal protection for criminal acts of trafficking in persons is generally regulated in various laws and regulations in Indonesia. The legal protection policy is directed at several aspects, namely: restitution and compensation, counseling services and medical assistance, legal assistance, and information provision. Indonesia must have a regulation that can protect against problems arising from acts of human trafficking carried out between countries.